The Effects of Conflicts Handling in Teamwork of Hotel Industry Located in Northern Region of Malaysia - Yusuf, Bibi Noraini Bt Mohd; Anuar, Siti Norsyafawani Bt Shamsul (Journal of Asian Scientific Research, 2014)
Conflict is part and parcel of people’s awareness in all aspects of life. There are few key factors affecting conflict handling in any teamwork, such as leadership effectiveness, employee satisfaction, behavior/ personality, communication and lastly, the role of the gender. The paper’s primary contribution in conducting this study are firstly to find out factors that influence conflicts handling in teamwork of hotel industry in northern areas and secondly to examine the parties responsible before, during and after an event of conflict occurring in the teamwork. This research has selected the hotel industry as the subject study and has chosen hotels located in the northern regions of Malaysia for data collection exercise. This study applied the quantitative research methodology, involving random distribution of questionnaires to two-hundred (200) respondents from the subject areas. Five (5) hypotheses have been pre-established and tested by using a multiple regression analysis methodology. The results of the study revealed that two (2) hypotheses, the behavior/personality and the roles of gender, supported and influenced conflicts handling in the teamwork. The remaining three (3) other hypotheses, including leadership effectiveness, employee satisfaction and communications, showed negative correlations to conflicts handling in the teamwork. Findings and frameworks of this study shall be perceived as being useful as well as invaluable to candidates for further academic researches on same topics and helpful to top management, business executives and Human Resource Managers to design and increase their skills in handling of conflicts in order to improve overall teamwork performance. The study also serves as useful guidelines to any organization on how to apply effective strategic teamwork management tools in handling of conflicts in their organization.